Countermovement jump performance variables correlate with weightlifting performance in elite participants - Geiser, C.; Ahn, N.; Kipp, K. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
It is valuable to monitor athletes` training efficacy to better guide their conditioning and performance programs. In weightlifting, assessing 1RM routinely may require longer recovery and limit training. The purpose of this study was to identify associations between 1RM weightlifting performance and variables calculated from a maximal countermovement jump (CMJ). Force data were collected and variables calculated for seven elite weightlifters during CMJs. Maximum rate-of-force development (RFD) during the countermovement jump was associated with both Snatch (r^2 0.56, p=0.05) and Clean & Jerk (C&J) (r^2=0.49, p=0.08) performance. Eccentric time (r^2=0.55, p=0.06) and ecc-conc ratio (r^2=0.68, p=0.02) were correlated with C&J performance only. CMJ variables may provide expedient efficient feedback on athlete performance and conditioning in this sport.